Language, gender, and violence in Turreo Místico, by Cumbi Bustinza: Language, gender, and violence in Turreo Místico by Cumbi Bustinza (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2025)
Cumbi Bustinza's theatre play takes the tragic architecture of Shakespeare's Macbeth – ambition, destiny, crime, guilt and fall – and relocates it in the Buenos Aires suburbs, transforming it into an urban tragedy with street language, aesthetics of cumbia and marginal logic. This geographical and cultural transposition directly affects the language that -in the form of slang, insult, compliment or threat- takes a central place as an instrument for asserting identity, power and submission. Far from being just a means of communication, it is the field where gender hierarchies and social position are negotiated. Understood in this way, the word not only names violence, but also exercises it, preceding or accompanying physical violence.From the perspective of gender theory and contemporary critical thinking, this article aims to analyse how in Turreo místico language produces precarious subjectivities, vulnerable bodies and bonds marked by the conflict between desire and domination.
Keywords: theatre; language; violence; gender; marginality